Prognostic factors associated with mortality among patients receiving venovenous extracorporeal membrane oxygenation for COVID-19: a systematic review and meta-analysis. Issue 3 (March 2023) - Tran, Alexandre; Fernando, Shannon M; Rochwerg, Bram; Barbaro, Ryan P; Hodgson, Carol L; Munshi, Laveena; MacLaren, Graeme; Ramanathan, Kollengode; Hough, Catherine L; Brochard, Laurent J; Rowan, Kathryn M; Ferguson, Niall D; et al.
Summary: Background: Venovenous extracorporeal membrane oxygenation (ECMO) can be considered for patients with COVID-19-associated acute respiratory distress syndrome (ARDS) who continue to deteriorate despite evidence-based therapies and lung-protective ventilation. The Extracorporeal Life Support Organization has emphasised the importance of patient selection; however, to better inform these decisions, a comprehensive and evidence-based understanding of the risk factors associated with poor outcomes is necessary. We aimed to summarise the association between pre-cannulation prognostic factors and risk of mortality in adult patients requiring venovenous ECMO for the treatment of COVID-19. Methods: In this systematic review and meta-analysis, we searched MEDLINE and Embase from Dec 1, 2019, to April 14, 2022, for randomised controlled trials and observational studies involving adult patients who required ECMO for COVID-19-associated ARDS and for whom pre-cannulation prognostic factors associated with in-hospital mortality were evaluated. We conducted separate meta-analyses of unadjusted and adjusted odds ratios (uORs), adjusted hazard ratios (aHRs), and mean differences, and excluded studies if these data could not be extracted. We assessed the risk of bias using the Quality in Prognosis Studies tool and certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation approach. Our protocol was registered with the Open Science Framework registry, osf.io/6gcy2. Findings: Our search identified 2888 studies, of which 42 observational cohort studies involving 17 449 patients were included. Factors that had moderate or high certainty of association with increased mortality included patient factors, such as older age (adjusted hazard ratio [aHR] 2·27 [95% CI 1·63–3·16]), male sex (unadjusted odds ratio [uOR] 1·34 [1·20–1·49]), and chronic lung disease (aHR 1·55 [1·20–2·00]); pre-cannulation disease factors, such as longer duration of symptoms (mean difference 1·51 days [95% CI 0·36–2·65]), longer duration of invasive mechanical ventilation (uOR 1·94 [1·40–2·67]), higher partial pressure of arterial carbon dioxide (mean difference 4·04 mm Hg [1·64–6·44]), and higher driving pressure (aHR 2·36 [1·40–3·97]); and centre factors, such as less previous experience with ECMO (aOR 2·27 [1·28–4·05]. Interpretation: The prognostic factors identified highlight the importance of patient selection, the effect of injurious lung ventilation, and the potential opportunity for greater centralisation and collaboration in the use of ECMO for the treatment of COVID-19-associated ARDS. These factors should be carefully considered as part of a risk stratification framework when evaluating a patient for potential treatment with venovenous ECMO. Funding: None.